Peran Lingkungan Sekolah Dalam Pembentukan Karakter Siswa di SD Al Washilyah 15 Medan - Shoumi, Putri Nur; Yuris, Evicenna (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Character education is very important for students because it forms a better person. The formation of student character is influenced by family, community, and school factors. Schools are one of the main places in character formation because students spend a lot of time at school with teachers, peers, and other adults. This study aims to analyze the role of the school environment in shaping the character of students at SD Al Washliyah 15 Medan. The school environment, which includes social interactions, policies, facilities, and the involvement of teachers and staff, plays an important role in the formation of student character. This study uses a descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model, which involves data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that a positive school environment is able to shape character values such as discipline, responsibility, cooperation, and honesty in students. This conclusion is expected to provide insight for schools in strengthening the role of the school environment in shaping students' character as a whole.